A preparation method and application of carbon nitride catalyst

By preparing carbon nitride non -metallic catalysts, the unstable and mol proportional restrictions of existing catalysts when catalyzed glycerol carbonate was converted into glycerol carbonate, and efficient and stable reactions were achieved and suitable for industrial production.

CN119215959BActive Publication Date: 2025-01-28DEZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718055.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing catalysts have instability and molar ratio limitations when catalyzing the conversion of glycerol to glycerol carbonate, resulting in inefficient reactions.

Method used

By mixed with melamine and polytramamine, and baked it at a certain temperature, the carbon nitride non -metallic catalyst was prepared to increase the activity site of its surface and improve the catalytic performance.

Benefits of technology

This catalyst can efficiently catalyze glycerin into glycerin carbonate without adding solvents. The maximum conversion rate of glycerin reaches 97%, the yield of glycerin carbonate is as high as 86%, and the response conditions are mild, suitable for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215959B_ABST
    Figure CN119215959B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of catalytic technology, and specifically relates to a carbon nitride catalyst and a preparation method and application thereof, comprising the following steps: S1, mixing and grinding a precursor melamine and a modifier polyaspartic acid; S2, after the raw materials are mixed and ground, roasting them in an air atmosphere at a certain temperature to obtain a catalyst. The carbon nitride-based catalyst of the present invention can efficiently catalyze the conversion of glycerol to prepare glycerol carbonate without adding any solvent, and the maximum conversion rate of glycerol is as high as 97%, and the yield of glycerol carbonate is as high as more than 86%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and specifically relates to a carbon nitride catalyst and a preparation method and application thereof. Background Art

[0002] As important renewable carbon resources, the utilization and conversion of carbon dioxide and biomass have important practical significance for promoting green and low-carbon development. Glycerol is considered to be a promising low-cost biomass. Converting glycerol into other high-value chemicals is an important way to expand the biodiesel industry chain. Dimethyl carbonate (DMC) is an important CO 2 The downstream product is considered to be a green carbonylation reagent.

[0003] Glycerol carbonate (GC) is an important glycerol derivative. It is non-toxic, biodegradable, water-soluble, flammable and has a low evaporation rate. It can be used as a green chemical raw material. Glycerol carbonate can be synthesized from glycerol and different carbonyl sources, so there are different synthetic routes. Glycerol carbonate is prepared by reacting glycerol with dimethyl carbonate. The by-product methanol can be reacted with CO 2 Further reaction generates DMC, which has high atom economy. The preparation of GC by reacting biomass glycerol with DMC is a very promising negative carbon technology route, so it has important research value.

[0004] The catalysts currently being studied mainly include single metal oxides, composite metal oxides, hydrotalcites, double metal hydroxides, aluminates, alkali / alkali metal-based hybrid nanocomposites and other composite materials. Involving a variety of alkali metals, alkaline earth metals and transition metals such as K, Na, Ca, Ba, Mg, Al, Cu, and Zn. The alkaline composite metal oxide catalyst has the highest efficiency, but the catalyst is unstable due to the loss of active components and the transformation of the crystal phase. Secondly, due to the single active site of the catalyst, the molar ratio of DMC / glycerol must be between 3-5 to achieve the best reaction effect. In view of these problems, it is urgent to develop an efficient and stable non-metal-based catalyst suitable for the production of glycerol carbonate.

[0005] Graphitic carbon nitride (gC 3 N 4 ) is a unique 2D layered non-metallic material whose main unit is tris-s-triazine bridged by N atoms. These bridging N atoms can act as Lewis bases to participate in catalytic reactions. 3 N 4 There are also a large number of fatty amine species (uncondensed primary and secondary amines) at the edges of the graphite-like layers. The presence of these basic sites makes gC 3 N 4 It has become a very promising solid base catalyst. 3 N4 The basic sites on the surface are not abundant, so gC 3 N 4 The structure and surface properties of carbon nitride are synergistically regulated to increase the number of active sites on the carbon nitride surface, and to develop an efficient carbon nitride-based non-metal catalyst for the conversion of glycerol to prepare glycerol carbonate. Summary of the invention

[0006] The first object of the present invention is to provide a method for preparing a carbon nitride catalyst, comprising the following steps:

[0007] S1, mixing and grinding the precursor melamine and the modifier polyaspartic acid;

[0008] S2. After the raw materials are mixed and ground, they are calcined at a certain temperature in an air atmosphere to obtain a catalyst.

[0009] Furthermore, the mass ratio of melamine to polyaspartic acid is 3g:(1-6)g.

[0010] Furthermore, the calcination temperature is 300-600° C., and the calcination time is 30-360 min.

[0011] The present invention also provides application of the carbon nitride catalyst in a reaction of preparing glycerol carbonate using glycerol and dimethyl carbonate as raw materials.

[0012] Furthermore, the optimal reaction conditions are: reaction temperature of 80-150° C.; reaction time of 2-24 hours.

[0013] Furthermore, the amount of catalyst added is limited to (0.04-1.5) g of catalyst per 0.04 mol of glycerol; and the molar ratio of glycerol to dimethyl carbonate is 1:1-1:5.

[0014] The beneficial technical effects of the present invention are as follows:

[0015] The invention provides a catalyst for preparing glycerol carbonate by glycerol ester exchange, which has mild reaction, high efficiency, good stability and is regenerable.

[0016] The carbon nitride-based catalyst of the present invention can efficiently catalyze the conversion of glycerol to prepare glycerol carbonate without adding any solvent, the highest conversion rate of glycerol is as high as 97%, and the yield of glycerol carbonate is as high as more than 86%. The reaction process conditions are mild and environmentally friendly, suitable for current industrialization requirements, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the XRD pattern of the polyaspartic acid modified melamine catalyst obtained in Example 2;

[0018] Figure 2 This is the FTIR spectrum of the polyaspartic acid modified melamine catalyst obtained in Example 2. DETAILED DESCRIPTION

[0019] The chemical reagents involved in the following examples can be purchased from chemical reagent companies unless otherwise specified. The reaction products were detected by gas chromatography (GC-9790 plus), with a chromatographic column model of RB-5 and a FID detector.

[0020] The glycerol conversion rate and the selectivity of glycerol carbonate were calculated according to the following formula:

[0021]

[0022]

[0023] Example 1

[0024] 3 g of melamine and 1 g of polyaspartic acid were mixed and then ground. After grinding, they were wrapped with tin foil and calcined at 550° C. in a muffle furnace for 240 min. After natural cooling, the target catalyst was ground.

[0025] Example 2

[0026] 3 g of melamine and 1.2 g of polyaspartic acid were mixed and then ground. After grinding, the mixture was wrapped with tin foil and calcined at 550° C. in a muffle furnace for 240 min. After natural cooling, the target catalyst was obtained by grinding. Figure 1 The XRD pattern and FTIR spectrum of the polyaspartic acid modified melamine catalyst obtained in Example 2 are shown in Figure 2 The diffraction peak at 27.1° in the XRD spectrum corresponds to the diffraction peak of carbon nitride, and a new diffraction peak appears at 32.7°, indicating that polyaspartic acid is successfully grafted onto carbon nitride. The FTIR spectrum at 1614 cm -1 A sharp absorption peak appears due to -CH 2 In-plane bending vibration occurs; at 2144cm -1 The absorption peak at 2929 cm -1 A small absorption peak appeared, mainly due to -CH 2 Stretching vibration occurs; at 3413 cm -1 A broad absorption peak appeared at , which can be attributed to the stretching vibration peak of NH bond. The infrared results showed that the carbon nitride catalyst was successfully prepared by calcining melamine, and polyaspartic acid was successfully grafted into carbon nitride to prepare the amino acid modified catalyst.

[0027] Example 3

[0028] The difference between Example 3 and Example 1 is that 1.5 g of polyaspartic acid is added, and the other conditions are exactly the same.

[0029] Example 4

[0030] The difference between Example 4 and Example 1 is that 3 g of polyaspartic acid is added, and the other conditions are exactly the same.

[0031] Example 5

[0032] The difference between Example 5 and Example 1 is that 6 g of polyaspartic acid is added, and the other conditions are exactly the same.

[0033] Comparative Example 1

[0034] The difference between Comparative Example 1 and Example 1 is that 0 g of polyaspartic acid was added, and the other conditions were exactly the same.

[0035] Examples 1-5 and Comparative Example 1 explore the effect of the amount of polyaspartic acid added on the catalytic performance of the catalyst.

[0036] 0.1 g of the catalyst obtained in Examples 1-5 and Comparative Example 1, 0.04 mol of glycerol, and 0.08 mol of dimethyl carbonate were respectively put into a three-necked flask and reacted at 80° C. for 2 h. The product after the reaction and the catalyst were centrifuged, and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of the tetraethylene glycol solution were fixed to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis, and the reaction results are shown in Table 1.

[0037] Table 1 Effect of the amount of polyaspartic acid added on the catalytic performance of the catalyst

[0038]

[0039] With the increase of polyaspartic acid, the recovery of glycerol carbonate first increases and then decreases. The modification of a small amount of polyaspartic acid can increase the surface functionalized active sites and significantly improve the performance of carbon nitride catalysts. However, when there is too much polyaspartic acid, the active sites on the catalyst surface are over-covered or blocked, reducing the number of actually available active sites. The original catalytic properties of carbon nitride are partially suppressed, resulting in a decrease in the overall catalytic performance. During high-temperature calcination, excessive polyaspartic acid may cause uneven changes in the catalyst structure, such as local carbonization or destruction of the pore structure, thereby affecting the stability and performance of the catalyst.

[0040] Example 6

[0041] 3 g of melamine and 1.2 g of polyaspartic acid were mixed and ground, wrapped in tin foil, and calcined at 300 °C in a muffle furnace for 240 min. After natural cooling, the target catalyst was obtained by grinding and recorded as C-6.

[0042] Example 7

[0043] The difference between Example 7 and Example 6 is that the calcination temperature is 400° C., and the other conditions are exactly the same.

[0044] Example 8

[0045] The difference between Example 8 and Example 6 is that the calcination temperature is 600° C., and the other conditions are exactly the same.

[0046] Examples 2, 6-8 explore the effect of calcination temperature on catalyst performance.

[0047] 0.1 g of the above catalyst, 0.04 mol of glycerol, and 0.08 mol of dimethyl carbonate were placed in a three-necked flask and reacted at 80°C for 2 h. The product and the catalyst after the reaction were centrifuged and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of tetraethylene glycol solution were taken and diluted to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis. The reaction results are shown in Table 2.

[0048] Table 2 Effect of calcination temperature on catalyst performance

[0049]

[0050] As the calcination temperature increases, the glycerol conversion rate increases and the yield of glycerol carbonate increases. The reason is that as the temperature increases, more surface defects are introduced, which can increase the catalyst's adsorption capacity for reactants and the density of active sites, thereby improving the catalytic performance. In addition, high temperature helps heteroatoms (such as N from polyaspartic acid) to be more evenly doped into the carbon nitride substrate and optimize the electronic structure of the catalyst. However, if the temperature is too high, it will lead to the destruction of active sites, the collapse of pore structure, changes in electronic structure, and a decrease in catalyst stability. Therefore, the calcination temperature needs to be precisely controlled to strike a balance between enhancing catalyst performance and maintaining structural integrity.

[0051] Example 9

[0052] 3 g of melamine and 1.2 g of polyaspartic acid were mixed and ground, wrapped in tin foil, and calcined at 550°C in a muffle furnace for 360 min. After natural cooling, the target catalyst was obtained by grinding.

[0053] Example 10

[0054] The difference between Example 10 and Example 9 is that the calcination time is 30 minutes, and the other conditions are exactly the same.

[0055] Example 2 and Examples 9-10 are intended to explore the effect of calcination time on catalyst performance.

[0056] 0.1 g of the above catalyst, 0.04 mol of glycerol, and 0.08 mol of dimethyl carbonate were placed in a three-necked flask and reacted at 80°C for 2 h. The product and the catalyst after the reaction were centrifuged and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of tetraethylene glycol solution were taken and diluted to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis. The reaction results are shown in Table 3.

[0057] Table 3 Effect of calcination time on catalyst performance

[0058]

[0059] It can be seen from the above table that with the extension of the catalyst calcination time, the glycerol conversion first increases and then decreases, and the yield of glycerol carbonate also shows the same rule. Proper extension of the calcination time is conducive to the improvement of catalytic performance. With the extension of the catalyst calcination time, the catalyst precursor is fully decomposed, doped or forms the required carbon nitride crystal phase, making the structure of the catalyst more uniform and stable. Functional modification requires longer time to diffuse and evenly distribute, optimizing the catalytic performance of the material. With the extension of the calcination time, more lattice defects or vacancies are generated on the catalyst surface, providing additional active sites and improving the catalytic performance. However, with the further extension of the calcination time, the functional groups (such as amine, hydroxyl, and carboxyl) decompose or deactivate at high temperature for a long time, resulting in a reduction in active sites and a decrease in catalytic performance. Excessive destruction of the carbon nitride skeleton causes the carbon nitride material to undergo gradual decomposition or even complete carbonization, losing its original catalytic activity. In addition, long-term calcination causes sintering of the grains, and the size of the catalyst particles increases, resulting in a decrease in specific surface area and a decrease in the density of active sites.

[0060] Embodiment 11

[0061] 40 mg of the catalyst in Example 2, 0.04 mol of glycerol, and 0.08 mol of dimethyl carbonate were placed in a three-necked flask and reacted at 80°C for 2 h. The product and the catalyst after the reaction were centrifuged and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of the tetraethylene glycol solution were diluted to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis. The reaction results are shown in Table 4.

[0062] Example 12

[0063] The difference between Example 12 and Example 11 is that the amount of catalyst added is 1.5 g, and the other conditions are exactly the same. The reaction results are shown in Table 4.

[0064] The comparison of Examples 2 and 11-12 is used to explore the effect of the amount of catalyst on the catalytic performance.

[0065] Table 4 Effect of catalyst dosage on catalytic performance

[0066]

[0067] As the amount of catalyst added increases, the glycerol conversion rate increases and the glycerol carbonate yield increases, but increasing the amount of catalyst too much has limited improvement in catalytic performance. The reason is that too much catalyst causes the accumulation or agglomeration of catalyst particles in the system, limiting the diffusion and contact of reactants on the catalyst surface.

[0068] Embodiment 13

[0069] 0.1 g of the catalyst in Example 2, 0.04 mol of glycerol, and 0.04 mol of dimethyl carbonate were placed in a three-necked flask and reacted at 80°C for 2 h. The product and the catalyst after the reaction were centrifuged and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of the tetraethylene glycol solution were diluted to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis. The reaction results are shown in Table 5.

[0070] Embodiment 14

[0071] The difference between Example 14 and Example 13 is that the amount of dimethyl carbonate added is 0.2 mol, and the other conditions are exactly the same. The reaction results are shown in Table 5.

[0072] The comparison of Examples 2 and 13-14 is used to explore the effect of the amount of dimethyl carbonate on the catalytic performance.

[0073] Table 5 Effect of the amount of dimethyl carbonate on the catalytic performance

[0074]

[0075] Increasing the amount of dimethyl carbonate can significantly improve the catalytic performance of the catalyst, but increasing the amount of dimethyl carbonate too much is not conducive to the requirements of the development of atom economy.

[0076] Embodiment 15

[0077] Take 0.1 g of the catalyst in Example 2, 0.04 mol of glycerol, and 0.08 mol of dimethyl carbonate into a three-necked flask and react at 80°C for 24 hours. The product and the catalyst after the reaction were centrifuged and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of the tetraethylene glycol solution were diluted to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis. The reaction results are shown in Table 6.

[0078] Example 16

[0079] The difference between Example 16 and Example 15 is that the reaction time is 0.5 h, and the other conditions are exactly the same. The reaction results are shown in Table 6.

[0080] The comparison of Examples 2, 15-16 is used to explore the effect of reaction time on catalytic performance.

[0081] Table 6 Effect of reaction time on catalytic performance

[0082]

[0083] Prolonging the reaction time can significantly increase the glycerol conversion rate, but as the reaction time continues to increase, the selectivity of glycerol carbonate decreases. Although prolonging the reaction time increases the glycerol conversion rate, it also leads to enhanced side reactions, reduced catalyst selectivity, and changes in chemical equilibrium, thereby reducing the selectivity of glycerol carbonate.

[0084] Embodiment 17

[0085] 0.1 g of the catalyst in Example 2, 0.04 mol of glycerol, and 0.08 mol of dimethyl carbonate were placed in a three-necked flask and reacted at 50°C for 2 h. The product and the catalyst after the reaction were centrifuged and the obtained liquid mixture was subjected to rotary evaporation. 0.2 g of the rotary evaporation liquid and 0.2 g of the tetraethylene glycol solution were diluted to a 10 mL volumetric flask with anhydrous ethanol for analysis. The prepared reaction solution was injected into a gas chromatograph for qualitative and quantitative analysis. The reaction results are shown in Table 7.

[0086] Embodiment 18

[0087] The difference between Example 18 and Example 17 is that the reaction temperature is 150°C, and the other conditions are exactly the same. The reaction results are shown in Table 7.

[0088] The comparison of Examples 2 and 17-18 is used to explore the effect of reaction temperature on catalytic performance.

[0089] Table 7 Effect of reaction temperature on catalytic performance

[0090]

[0091] As the reaction temperature increases, the glycerol conversion first increases and then decreases. Properly increasing the reaction temperature is beneficial to the glycerol conversion. However, when the temperature is increased to 150°C, the gasification rate of dimethyl carbonate is accelerated, which is not conducive to the conversion of glycerol into glycerol carbonate.

[0092] In summary, the carbon nitride-based non-metallic catalyst of the present invention can efficiently catalyze the conversion of glycerol to prepare glycerol carbonate under solvent-free and relatively mild reaction conditions. The use of the above catalyst can effectively reduce environmental pollution, the catalyst is easy to recycle, the maximum conversion rate of glycerol carbonate is as high as 97.2%, and the yield of glycerol carbonate is as high as more than 86%. The catalyst of the present invention has low equipment requirements, convenient catalyst regeneration, and is suitable for industrial production.

Claims

1. An application of a carbon nitride catalyst in the reaction of preparing glycerol carbonate using glycerol and dimethyl carbonate as raw materials, characterized in that: The method for preparing the carbon nitride catalyst comprises the following steps: S1, mixing and grinding the precursor melamine and the modifier polyaspartic acid; S2, after the raw materials are mixed and ground, they are calcined in an air atmosphere to obtain a catalyst; In step 1, the mass ratio of melamine to polyaspartic acid is 3 g:(1-6) g; In step 2, the calcination temperature is 300-600° C. and the calcination time is 30-360 min.

2. The use of the carbon nitride catalyst according to claim 1 in the reaction of preparing glycerol carbonate using glycerol and dimethyl carbonate as raw materials, characterized in that: The reaction temperature is 80-150°C; the reaction time is 2-24 hours.

3. The use of the carbon nitride catalyst according to claim 1 in the reaction of preparing glycerol carbonate using glycerol and dimethyl carbonate as raw materials, characterized in that: The amount of catalyst added is limited to (0.04-1.5) g of catalyst per 0.04 mol of glycerol; the molar ratio of glycerol to dimethyl carbonate is 1:1-1:5.

Citation Information

Patent Citations

  • Preparation method of oxygen-sulfur dual-doped graphite phase carbon nitride

    CN108786878A

  • Method for producing nitrogen-containing carbon porous material

    JP2017186207A